Microcomputed Tomography Evaluation of Root Dentin Caries Prevention by Topical Fluorides and Potassium Iodide - Zander, Vernon (Sensors (Basel), 2019)
The mineral content of dental hard tissues has traditionally been measured by destructive tests such as transverse microradiography. Microfocus X-ray computed tomography (micro CT) has enabled non-destructive 3D assessment of tooth demineralization. This study compared the preventive effects of silver diammine fluoride (SDF) and potassium iodide (KI) in comparison with fluoride varnish. SDF has been known to arrest caries but darkens the tooth. KI creates a precipitate with SDF that reduces the discoloration, but its effects on SDF efficacy in terms of preventing demineralization of at-risk root dentin surfaces is unknown. Bovine root dentin blocks were randomly distributed into four groups and subjected to a pretreatment in each group (n = 8); Control: deionized water (DIW); F-Varnish: 5% sodium fluoride varnish: 38% Saforide; SDF+KI: SDF followed by saturated solution of KI in DIW. The treated dentin was subjected to 8 cycles of demineralization (pH 5) for 14 h and remineralization in artificial saliva (pH 7) for 10 h. Specimens were then scanned for 12 min using micro CT at 73 KV and 1012 µA with 8.3 μm resolution. The 3D images were analyzed in Amira software to calculate lesion depth (LD), surface layer mineral density (SL) and mineral loss (ΔZ) for each specimen. One-way ANOVA with Bonferroni posthoc showed that there was a statistically significant difference between Control and all three other groups for all parameters (P < 0.001), however, there was no statistical difference among F-Varnish, SDF and SDF+KI (P > 0.05). Single application of F-Varnish, SDF and SDF+KI showed comparable preventive effects against root dentin demineralization. Application of KI did not affect anti-demineralization properties of SDF in this study. Micro CT is a quick and effective method for objective and high-resolution characterization of dentin caries lesions.